Retrospective Study: Characteristic of Papular Pruritic Eruption in HIV/AIDS Patients - Arista, Afria; Murtiastutik, Dwi (Faculty Of Medicine Airlangga University, 2015)
Background: Acquired immunodeficiency syndrome(AIDS) is a symptoms caused by infection of Human immunodeficiency virus (HIV) that may cause the decreasing of immune system. Skin disorder that can occurin patients with AIDS are papular pruriticeruption (PPE), which often lead toimpaired quality of lifein patients. Purpose: To evaluate the general overview and management of PPE, hence better management can be provided. Methods: Retrospective study of PPE patien in UPIPI (Unit Perawatan Intermediate Penyakit Infeksi) Dr. Soetomo General Hospital Surabaya during 2014. Results: The number of PPE patients was 15.4% of hospitalized patients. The largest age group was 25-44 years (56.9%), sex most were male (65.5%). Patients mostly from Surabaya (72.4%). Most of the patients worked asprivate sector workers (43.1%), and 73.2% of those with high school education. The main complaints include itching (83.62%), the location is in the limbs (55.2%). The most effloresensi is +multiplepapuleshyperpigmentation sharply marginated (58.6%). Mosttypes oftransmissionarefree sex (78%), CD4 highest 3value is 1-100 cells/mm (32.7%), 56.9% of patients received ARV treatment. Skin treatment is topical steroids (73.3 %). Conclusion: PPE is a skin disorderthat often arises in patients with HIV/AIDS.Keywords: papular pruritic eruption , HIV/AIDS, retrospective.